2015
DOI: 10.1002/ccr3.265
|View full text |Cite
|
Sign up to set email alerts
|

Potentially lethal ACE‐inhibitor‐induced angioedema in a child

Abstract: Key Clinical MessageWe report a case of a 9-year-old female with known end-stage kidney disease who presented with sudden onset tongue swelling. A diagnosis of angiotensin-converting enzyme inhibitor-induced angioedema related to bradykinin accumulation was made. Her symptoms resolved shortly after discontinuation of captopril. Early diagnosis can save patients from severe upper airway obstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…This problem is an atypical occurrence in Saudi Arabia, as only one case has been reported [ 6 ]. Moreover, when we inquired of the National Pharmacovigilance and Drug Safety Center at the Saudi Food and Drug Authority regarding this, they stated that only four cases of angioedema induced by either lisinopril, captopril, or perindopril have been documented.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This problem is an atypical occurrence in Saudi Arabia, as only one case has been reported [ 6 ]. Moreover, when we inquired of the National Pharmacovigilance and Drug Safety Center at the Saudi Food and Drug Authority regarding this, they stated that only four cases of angioedema induced by either lisinopril, captopril, or perindopril have been documented.…”
Section: Discussionmentioning
confidence: 99%
“…So far, only four cases of angioedema caused by ACE inhibitors have been reported to the National Pharmacovigilance and Drug Safety Center at the Saudi Food and Drug Authority by different hospitals in Saudi Arabia. In 2015, Bukhari et al [ 6 ] reported the first study regarding the occurrence of angioedema following administration of ACE inhibitors in a 9-year-old girl with renal disease. The rarity of this condition in Saudi Arabia may be because the predisposing factors are still unknown, although it is more common among African-American patients.…”
Section: Introductionmentioning
confidence: 99%
“…ACEI-induced angioedema (ACEI-AE) is characterized by non-pitting edema of the skin and/or mucous membranes, most commonly in the head and neck area, often involving swelling of the lips and/or tongue [1]. ACEI-AE has mainly been reported in adults, with few reports in children [2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%